Kedudukan Keputusan Pemerintah dalam Keadaan Darurat Digital Studi tentang Batasan Konstitusional atas Kebijakan Cyber Emergency - Maulana Fahmi Idris; Althea Serafim Kriswandaru (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
The rapid growth of digital technology has created new challenges for the constitutional framework of state power, particularly in the context of cyber emergencies. This research analyzes the role of government decisions in digital emergencies within the framework of Indonesian constitutional law. Using a socio-legal approach, the study examines the alignment between governmental actions and fundamental constitutional principles, such as legality, proportionality, accountability, and the protection of human rights. The findings reveal significant gaps between existing regulations and the need for constitutionally grounded responses to cyber threats. Current government measures tend to be reactive and lack comprehensive oversight mechanisms, posing risks to democratic governance and individual rights. The study recommends establishing a specific legal framework that clearly defines procedures, limitations, and oversight for cyber emergency actions, grounded in digital constitutionalism. By reinforcing constitutional supremacy in the digital era, the government can ensure that its responses to cybersecurity crises are both effective and respectful of citizens' fundamental rights.